Conservação a longo prazo de grãos de pólen de Paspalum notatum Flüggé visando o uso de espécies de florescimento assíncrono em programas de melhoramento genético - Dinato, Naiana Barbosa (Universidade Federal de São Carlos, 2016)
Paspalum is the most important genus of Poaceae family in the Americas, with about 330 species and occurs throughout Brazil, Bolivia, Paraguay, Argentina and Uruguay. In Brazil, except for the Pampa Biome, the use of species of this genus as a cultivated forage is still very small. Species of the informal group Plicatula are among the most promising Paspalum genotypes for forage quality. The majority of Paspalum accessions is tetraploid and apomitic. The sexual cytotypes are rare in the Plicatula group. To add features located in different accessions, it is necessary to cross sexual species in tetraploid level with apomictic genotypes that are interesting to breeding programs and select those that have better agronomic characteristics. For the occurence of hybridization, the flowering synchronization betwemn parents is essencial. An interesting tool for this is the cryopreservation of pollen. P. notatum, popularly known as bahiagrass, is a species from Notata group and is widely used in the United States as forage. Diploid and tetraploid accessions are observed in this species and, it is easy to obtain large amounts of pollen. The purpose of this study was to evaluate the cryopreservation of pollen of P. notatum, as a model for future conservation and synchronization of flowering of other species that are interesting for breeding program. The P. notatum pollen grains were collected in the field at Embrapa Southeast Livestock. Four dehydrating agents were tested (LiCl, MgCl2, NaOH and Silica gel) with three distinct periods of exposion (30, 60 and 120 minutes). After slow thawing, pollen grains were evaluated for viability by staining with tetrazolium solution 0.25% and in vivo germination by fluorescence. The viability of fresh pollen grains was also evaluated as a control. For comparison, pollen grains were stored in freezer and refrigerator conditions for a period of 10, 60, 120 and 180 days. The data showed that the dehydration of Paspalum notatum pollen with lithium chloride during 30 minutes and silica gel during 120 minutes was adequated for the conservation in liquid nitrogen and freezer as the viability of pollen after this treatment remained equal to the control. The pollen preservation in the refrigerator without dehydration since 10 days may be an alternative for short-term storage situations. Dehydration results with dehydrated magnesium chloride for 30 and 60 minutes and dehydrated sodium hydroxide for 60 and 120 9 minutes were also statistically similar to the control. The use of the tetrazolium sollution and in vivo germination were an effective technique to evaluate the viability of pollen grains after liquid nitrogen conservation. The use of tetrazolium was also efficient for the evaluation of pollen grains after storage in freezer and refrigerator.
LONG-TERM PRESERVATION OF POLLEN GRAINS of Paspalum notatum FLÜGGÉ AIMING THE USE OF ASYNCHRONOUS FLOWERING SPECIES IN GENETIC BREEDING PROGRAMS
Keywords: Forrageiras; Criopreservação; Solução salina saturada; Nitrogênio líquido; Forage crop; Cryopreservation; Saturated salt solution; Liquid nitrogen; CIENCIAS BIOLOGICAS